1963
DOI: 10.2466/pr0.1963.13.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Does Training with Differential Reinforcement on Similar Problems Help in Solving a New Problem?

Abstract: An experiment to determine, for achieving correct solutions to the Hatrack Problem whether prior experience on a simpler version of the problem helps and the effects of positive and negative reinforcement. After 30 min., 50.0% of the 30 Ss with no experience but only 25.0% of the 60 Ss with experience on the simpler version solved the problem ( p < .05). Positive and negative reinforcement showed no differential effects for 30 Ss receiving each. Previous experience may inhibit productive problem solving by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1965
1965
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Mindfulness is a style of thinking that typically conflicts with one's fixed mindset that is counterproductive to aspects of problem solving (Hoffman et al, 1963;Luchins, 1942) and social cognition (Bargh, Chen, & Burrows, 1996;Lane & Piercy, 2003). Mindfulness has been characterized by Langer and colleagues as a mental state in which individuals divide their attention into novel distinctions of objects (e.g., in a traditional mindset condition, people are likely to impose stigma on the disabled; in contrast, under the state of mindfulness condition, people might think that individuals with a physical disability are suitable for sitting work from multiple perspectives).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mindfulness is a style of thinking that typically conflicts with one's fixed mindset that is counterproductive to aspects of problem solving (Hoffman et al, 1963;Luchins, 1942) and social cognition (Bargh, Chen, & Burrows, 1996;Lane & Piercy, 2003). Mindfulness has been characterized by Langer and colleagues as a mental state in which individuals divide their attention into novel distinctions of objects (e.g., in a traditional mindset condition, people are likely to impose stigma on the disabled; in contrast, under the state of mindfulness condition, people might think that individuals with a physical disability are suitable for sitting work from multiple perspectives).…”
Section: Introductionmentioning
confidence: 98%
“…In some cases, these old thinking patterns, to some degree, cannot adapt absolutely and effectively to new problems, and may even impede our ability to think creatively and critically. A substantial body of literature on the Einstellung effect (Hoffman, Burke, & Maier, 1963;Luchins, 1942) has indicated people's predisposition to fall into a rigid and constrained mind-set using traditional problem-solving pattern(s) and even ignoring other simpler and better solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the Einstellung effect or set has clearly shown how quickly people come to respond to the world in a limited and rigid fashion. The now classic water jar studies by Luchins (1942) have served as an appropriate model of this behavior (more recent work by Hoffman, Burke, & Maier, 1963, made essentially the same point). After brief experience with one solution to a problem, subjects tend to overlook a simpler solution (or more effective solution, as in the case of Hoffman et al, 1963) when it is available and appropriate.…”
mentioning
confidence: 99%
“…The now classic water jar studies by Luchins (1942) have served as an appropriate model of this behavior (more recent work by Hoffman, Burke, & Maier, 1963, made essentially the same point). After brief experience with one solution to a problem, subjects tend to overlook a simpler solution (or more effective solution, as in the case of Hoffman et al, 1963) when it is available and appropriate. Luchins (1942) found that although subjects were more flexible when instructed to think about the problem carefully, they were still somewhat rigid.…”
mentioning
confidence: 99%
“…Previous research with the Hatrack Problem (Hoffman, Burke, & Maier, 1963) has indicated two common incorrect assumptions which Ss tend to make in trying to solve the problem: (1) a hatrack is a vertical strucmre which rests on the floor and ( 2 ) the coat must be hung at the end of one of the sticks. Both assumptions conflict with finding the correct solution, which requires the use of the ceiling as a support for the structure and the clamp both as the coat hanger and as a fastener for the two sticks.…”
Section: Ex~erimelztal P~oblemmentioning
confidence: 99%